Pohyby očí, selektívna pozornosť a profesijné videnie učiteľov a učiteliek - Silvia Harvanová; Lenka Sokolová; Miroslava Lemešová; Zlatica Jursová Zacharová; Patrik Hlaváč; Katarína Minarovičová (Karolinum Press, 2020)
The assumption, that the experimental research using eye-tracking technology, is the exclusive part of cognitive psychology and neurosciences domain, is not valid anymore. The interest in scanning eye movements has spread into many fields of applied research, including educational psychology. Present study focuses on the eye-tracking data potential for more complex understanding of attentional processes that constitute an important part of teachers' professional vision. The essential selective attention mechanisms are linked with eye movements and professional vision and analyzed from the interdisciplinary point of view. Firstly, the mechanisms of visual attention and eye movements are discussed with an emphasis on attentional selectivity as an important visual orientation tool. Secondly, the essential characteristics of eye-tracking as a methodological tool are introduced. Thirdly, the concept of professional vision is discussed in the attentional context. The last part represents a review of eye-tracking research in educational psychology, with a focus on the professional vision by comparing pre-service teachers with expert teachers. In conclusion, the potential of eye-tracking use in similar studies and its implications for attentional processes and pre-service teachers training are discussed.